Phenology of vernonia polyanthes less. In native population - Gomes, Jordany A. de O. [UNESP]; Bonfim, Filipe P. G. [UNESP]; Teixeira, Daniela A. [UNESP]; Martins, Ernane R. (My University, 2019)
Vernonia polyanthes Less. stands out as one of plants of interest of the Brazilian Unified Health System. It is known as “assa-peixe” in Brazil and it has therapeutic properties such as antihypertensive and diuretic, antifungal and antimicrobial. Understanding the life cycle of the species can provide information for management programs and the conservation of genetic resources. The objective of this study was to determine the phenological behavior of V. polyanthes, in a Cerrado area, to evaluate the effect of the climatic variables of the place during each phenophase, and to evaluate the synchrony of these phenophases among individual plants as well. Forty individuals were evaluated monthly from August 2014 to August 2016, regarding the intensity and synchrony of phenophases of budding, mature leaves, leaf senescence, leaf fall, flowering and fruiting. The species studied showed seasonal phenological behavior with annual periodicity, where synchrony among the individuals evaluated over 24 months was high. This one factor is a facilitator of species management. Mean temperature was the abiotic factor that most influenced the phenophases. Assa-peixe flowered in the period of June to August, while fruiting reaching peak intensity in the month of October.
Fenología de vernonia polyanthes less. En población nativa
Keywords: Assa-peixe; Cerrado; Species management